2019
DOI: 10.3389/fmars.2019.00712
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an Advective Marine Heatwave in the Middle Atlantic Bight in Early 2017

Abstract: There has been wide interest in Marine Heatwaves and their ecological consequences in recent years. Most analyses have focused on remotely sensed sea surface temperature data due to the temporal and spatial coverage it provides in order to establish the presence and duration of Heatwaves. Using hydrographic data from a variety of sources, we show that an advective Marine Heatwave was initiated by an event in late December of 2016 south of New England, with temperature anomalies measuring up to 6 • C and salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 27 publications
(50 reference statements)
3
62
0
1
Order By: Relevance
“…Studies such as Myers and Drinkwater (1989) can be revisited to understand the impact of the larger number of WCRs (after the regime shift in 2000) on the various groundfish populations in the GOM and GB area. In fact, such a high number of WCRs in the slope water might have impacted the ecosystem of the GOM/GB and MAB by making them even warmer and saltier frequently in the first two decades of the 21st century as reported recently by Gawarkiewicz et al (2019). An investigation for identifying similar regime shift in the recruitment structure of ichthyoplankton and zooplankton is underway.…”
Section: 1029/2019jc016033mentioning
confidence: 90%
“…Studies such as Myers and Drinkwater (1989) can be revisited to understand the impact of the larger number of WCRs (after the regime shift in 2000) on the various groundfish populations in the GOM and GB area. In fact, such a high number of WCRs in the slope water might have impacted the ecosystem of the GOM/GB and MAB by making them even warmer and saltier frequently in the first two decades of the 21st century as reported recently by Gawarkiewicz et al (2019). An investigation for identifying similar regime shift in the recruitment structure of ichthyoplankton and zooplankton is underway.…”
Section: 1029/2019jc016033mentioning
confidence: 90%
“…Large amplitude meanders and WCRs can bring warm salty water into close proximity to the continental slope and shelf break 11 , 12 and can affect both the Shelfbreak Jet as well as shelf temperature 13 . Gawarkiewicz et al 14 found that an ocean-driven MHW along the continental shelf of the Mid-Atlantic Bight in 2017 was forced by the presence of a WCR, which resulted in cross-shelf transport of warm and salty Gulf Stream water. Additionally, a northward shift of the Gulf Stream toward the Tail of Grand Banks, where it potentially blocks the equatorward-flowing Labrador Current has been shown to increase salinity and temperature of subsurface waters on the Northwest Atlantic Shelf, “downstream” (southwest) of this interaction location 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…This path variability has been linked to multiple processes spanning from fisheries (Nye et al., 2011) to atmospheric events (Joyce et al., 2009) and is often interpreted as an indicator of climate change (Caesar et al., 2018; Zhang et al., 2019). In particular recent rapid changes in the northwest Atlantic water properties and ecosystem, responses have been linked to the variations of the GS path and its instabilities (Andres, 2016; Brickman et al., 2018; Gangopadhyay et al., 2019; Gawarkiewicz et al., 2012, 2018, 2019; Mills et al., 2013; Pershing et al., 2015; Silver et al., 2021).…”
Section: Introductionmentioning
confidence: 99%